2021
DOI: 10.3389/fvets.2021.678536
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Modified GH11 Xylanase on Live Performance, Gut Health, and Clostridium perfringens Excretion of Broilers Fed Corn-Soy Diets

Abstract: Xylanase enzymes and other feed additives are being used more commonly in poultry feed to reduce feed cost, improve performance, and maintain gut health. Five corn-soy-based dietary treatments were designed to compare the effect of different inclusion levels of high-efficiency GH11 xylanase on live performance, gut lesions, and Clostridium perfringens excretion in littler samples of broiler chickens. Diets were the standard diet (positive control; PC); a diet of reduced energy by 130 kcal/kg diet (negative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…The increased body weight gain and reduced FCR value seen in the starter phase of birds fed the corn-based diets as a result of applying the higher xylanase dose is in agreement with Nusairat and Wang (2021) , who saw linear improvements in both parameters in the starter phase with increasing xylanase concentration in birds fed corn-based diets Van Hoeck et al. (2021) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The increased body weight gain and reduced FCR value seen in the starter phase of birds fed the corn-based diets as a result of applying the higher xylanase dose is in agreement with Nusairat and Wang (2021) , who saw linear improvements in both parameters in the starter phase with increasing xylanase concentration in birds fed corn-based diets Van Hoeck et al. (2021) .…”
Section: Discussionsupporting
confidence: 83%
“…This was based on a number of studies observing increased performance when feeding higher xylanase doses. For example, Nusairat and Wang (2021) saw improved BWG at d 1 to 42 when feeding 15 XU/g compared to 10 XU/g xylanase, Van Hoeck et al. (2021) saw reduced FCR at d 0 to 35 when feeding 90,000 BXU/kg compared to 30,000 BXU/kg xylanase, and Liu and Kim (2017) found body weight increased and FCR decreased linearly with increasing xylanase level ranging from 0 to 5,625 XU/kg xylanase at d 1 to 18.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that approximately an additional 450 kcal of digestible energy per kilogram of feed remains unutilized due to NSPs [ 6 ]. Several studies have shown that exogenous enzymes such as xylanase can release energy from the fiber fractions in the cell wall of corn, wheat and other ingredients, resulting in fewer nutrients available for opportunistic microorganisms in the lower gut and, subsequently, improving broiler performance and return on investment [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Van Hoeck et al (2021) found that feeding 90,000 U/kg xylanase resulted in higher caecal volatile fatty acid concentration and digestibility of organic matter, protein, fat, acid detergent fibre and energy, coupled with a lower FCR value, compared to feeding 30,000 U/kg xylanase. Moreover, Nusairat and Wang (2021) observed that feeding 15 XU/g xylanase was advantageous over feeding 10 XU/g in terms of body weight gain (BWG) at d 1-42 and apparent metabolisable energy at d 21 and 42, when supplemented into reduced-energy diets, and Singh et al (2021) observed a linear increase in body weight gain when feeding 0, 8,000 and 16,000 BXU/kg xylanase. Conversely, Olukosi et al (2007) saw no differences in performance between feeding 3,200 and 32,000 U/kg xylanase to broiler chickens fed wheat-ryesoybean meal-based diets.…”
Section: Introductionmentioning
confidence: 99%